Undergraduate Disabled Students as Knowledge Producers including Researchers: A Missed Topic in Academic Literature - Aspen Lillywhite; Gregor Wolbring (MDPI AG, 2019)
Research experience is beneficial for undergraduate students for many reasons. For example, it is argued in academic literature and in reports produced by various organizations that engage with science, technology, engineering and math (STEM) education and science education that undergraduate research experience increases the graduation rate in STEM disciplines as well as the amount of students thinking about STEM careers. As such, being researchers should also be of benefit to undergraduate disabled students in all disciplines including STEM education. However, given that undergraduate disabled students encounter many problems within post-secondary education, including STEM education, undergraduate disabled students might encounter problems in becoming researchers. Policies are to be guided by knowledge and evidence. However, knowledge and evidence deficits exist in relation to the lived experience of disabled people. Undergraduate disabled students could decrease the knowledge deficit as researchers and knowledge producers. The numbers of disabled academic faculty are judged as being too low and efforts are under way to increase the number of disabled academics. Increasing the number of undergraduate disabled researchers might increase the available pool of disabled students that pursue an academic career. Given the important role research performed by undergraduate disabled students can play and given that many studies highlight problems for disabled students in post-secondary education in general, we used a scoping review approach to investigate the coverage of undergraduate disabled students as knowledge producers, including as researchers, in the academic literature. Using various search strategies, we obtained 1299 initial hits. However, only 15 had relevant content. No study investigated how undergraduate disabled students select their research topics or how they are enticed to pursue research projects outside of a course-based framework. No study looked at the linkage between being an undergraduate disabled researcher and career choices or using the obtained research skills on the undergraduate level in one's role as a community member after graduation. Our findings suggest an opportunity for many fields, ranging from disability studies to STEM education, to generate more empirical data and conceptual work on the role of undergraduate disabled students as knowledge producers including as researchers. Such studies could help to increase the numbers of undergraduate disabled students as knowledge producers, including researchers, which in turn could help to increase (a) the number of disabled academics, (b) the number of disabled students who perform research in the community after graduation, (c) the degree success of disabled students and (d) the knowledge available on the social situation of disabled people.